Prevalence of Vitamin D deficiency among pregnant women and effect of Vitamin D supplementation on maternal and fetal outcomes: A double-blind randomized placebo controlled trial - Aggarwal, Neelam; Singla, Rimpi; Dutta, Usha; Bhadada, Sanjay Kumar; Dutta, Sourabh; Dhaliwal, Lakhbir; Garg, Sukant (Asian Journal of Medical Sciences, 2022)
Background: Vitamin D deficiency (VDD) in pregnancy has been found to be associated with adverse outcome in various observational studies. Evidence from randomized control trials is necessary to change current recommendations. Aims and Objectives: We conducted randomized controlled trial to assess the effect of Vitamin D supplementation on pregnancy outcome. We also looked for predictors of VDD as universal testing is neither recommended nor available. Materials and Methods: Consecutive pregnant women at 12–16 weeks of gestation were invited to participate in the study. Eligible women were assessed for potential risk factors for VDD (serum concentration <20 ng/dl). Serum 25-OH Vitamin D levels were checked. At 20 weeks gestation, consenting women (n=297) were randomized to receive either 60,000 IU Vitamin D (n=151) orally daily for 5 days or placebo (n=146). Maternal and fetal outcomes were compared between the two groups by intention-to-treat analysis. Results: Out of 304 eligible women, 92% had VDD. Mean Vitamin D concentration was 10.04±6.03 ng/dl. Vitamin D concentration was lower among women living in urban areas (P=0.001) and having lower sun exposure time (P=0.013). Vitamin D levels showed negative correlation with socioeconomic score (ρ=−0.131; P=0.023) and BMI (ρ=−0.112; P=0.05). In placebo group, women with VDD had longer duration of labor than Vitamin D replete ones (P=0.031). No significant difference was observed between two groups with respect to maternal and fetal outcomes. No adverse effects were observed. Conclusion: VDD is highly prevalent among pregnant women. It is associated with significantly longer duration of labor.